The Students’ Attitudes towards the Use of Code Switching and the Different Types that Occur in Speech - KELKOULA, Nachoua; DJAILEB, Farida (Journal of Human Sciences, 2019)
This work aims at investigating the different types of code switching and the students’ attitudes towards the use of this phenomenon. The study is conducted at the department of Letter and Arabic languages, ENSC in Constantine and it involves 50 speaking students to answer the questionnaire concerning the attitudes of using code switching and a direct observation is made in which it entails the researcher to assist to different sessions and recording the conversations in order to identify the different types of code switching that occur during the interactions.